2018
DOI: 10.3389/fnbeh.2018.00313
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Affective Rivalry: A Behavioral and fMRI Study Combining Olfactory and Auditory Stimulation

Abstract: Aversive odors are highly salient stimuli that serve a protective function. Thus, emotional reactions elicited by negative odors may be hardly influenceable. We aim to elucidate if negative mood induced by negative odors can be modulated automatically by positively valenced stimuli. We included 32 healthy participants (16 men) in an fMRI design combining aversive and neutral olfactory stimuli with positive and neutral auditory stimuli to test the influence of aversive olfactory stimuli on subjective emotional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 90 publications
(141 reference statements)
1
11
0
Order By: Relevance
“…The first olfactory pulse was administered jittered at random with a delay of 1.0, 1.5, 2.0, or 2.5 s relative to the beginning of the auditory stimulus, so always after the fade-in period was completed. The administration of the stimuli combination was followed by three ratings (duration 11 s, 3.66 s per rating) and a baseline period (duration 5 s), where a fixation cross was shown [ 13 ] …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The first olfactory pulse was administered jittered at random with a delay of 1.0, 1.5, 2.0, or 2.5 s relative to the beginning of the auditory stimulus, so always after the fade-in period was completed. The administration of the stimuli combination was followed by three ratings (duration 11 s, 3.66 s per rating) and a baseline period (duration 5 s), where a fixation cross was shown [ 13 ] …”
Section: Resultsmentioning
confidence: 99%
“…Relations with behavioural ratings that were found in the previous study, indicated that modulation of brain activation in these areas may also guide conscious labelling of emotional state and valence of external stimuli. Thus, as discussed earlier these areas may link integratory brain activation to emotional experience and therefore play a central role on implicit emotion regulation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations